Federally mandating motorcycle helmets in the United States. (December 2016) - Eltorai, Adam; Simon, Chad; Choi, Ariel; Hsia, Katie; Born, Christopher; Daniels, Alan
Abstract Background Motorcycle helmets reduce both motorcycle-related fatalities and head injuries. Motorcycle crashes are a major public health concern which place economic stress on the U.S. healthcare system. Discussion Although statewide universal motorcycle helmet laws effectively increase helmet use, most state helmet laws do not require every motorcycle rider to wear a helmet. Herein, we propose and outline the solution of implementing federal motorcycle helmet law, while addressing potential counterarguments. Conclusions The decision to ride a motorcycle without a helmet has consequences that affect more than just the motorcyclist. In an effort to prevent unnecessary healthcare costs, injuries, and deaths, public health efforts to increase helmet use through education and legislation should be strongly considered. Helmet use on motorcycles fits squarely within the purview of the federal government public health and economic considerations.